EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN BERGAMBAR TERHADAP HASIL BELAJAR DI SMK PANCA BHAKTI SUNGAI RAYA - Yulianti Yulianti; Bambang Genjik; Husni Syahrudin (Universitas Tanjungpura, 2020)
AbstractThis study aimed to determine the effectiveness of the students learning outcom of XI School of business subjects in SMK Panca Bhakti Sungai Raya before and after using illustrated learning media. The method used in this research was an experimental method with the form of Pre Experimental Design research. The population in this study was as much as 32 students and for samples using the entire population. The data collection used was the observation technique, measuring technique, documentary study technique. So researchers concluded that, the acquisition of pretests of students' learning results before using the Illustrated learning media of an average value of 48.125, postest student learning results after the average display learning media is increased to 70.781 and effectiveness of the use of pictorial learning media on learning outcom of XI business class on the subject of retail businesses using the test paired T sample test that was the value of the students learning results of-17.844 with the probability (SIG) 0.000 < 0.05 then H0 rejected and Ha accepted. This meant that the media was an effective study of the learning outcom of the students XI class in the retail business subjects at SMK Panca Bhakti Sungai Raya.Keywords: Effectiveness, Learning Media, Learning Outcome